Pricing in Oil Market and Using Probit Model for Analysis of Stock Market Effects - Mikhaylov, Alexey Yurievich (International Journal of Energy Economics and Policy, 2018)
The paper proposes the pricing in the oil market and the impact of oil prices on world stock indices. There is analysis of major trends in the oil market. We develop a model to predict the impact of oil prices on stock market indices for developed economies and Russia. This work propose a probit-model for forecasting capital markets trends using Brent pricing, three-month interest rates of the money market, consumer price index, GDP growth rate as a binary dependent variables. The trends of pricing in different stages of development of the oil market make the on stock indices, as developed countries and Russia. The practical significance of this work lies in the structuring of existing knowledge on the applicability of the probit-models in the context of the Russian economy. The paper also outlines the macroeconomic trends of supply and demand in the oil market and the characteristics of the modeling in the conditions of unstable economic situation in Russia. This work fills a gap in the use and implementation of the probit-models for the Russian economy. We make the forecast of supply and demand in the oil market in the next 1-3 years. We believe that oil prices are not likely to go up. The effect of oil prices on the stock markets is generally asymmetrical, except of the Russian and Canadian stock markets, because Russian and Canadian economies depend on oil export indeed. Keywords: oil price forecasting, stock market returns, probit-model. JEL Classifications: E37, F20, G15.